2019
DOI: 10.1039/c8nj05893h
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric, electroanalytical and theoretical evaluation of the antioxidant activity of Syzygium aromaticum L., Origanum vulgare L., Mentha spicata L. and Eremanthus erythropappus M. essential oils, and their major constituents

Abstract: Antioxidant mechanism of essential oils and their major constituents, and the synergism between them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Previous studies showed that only carvacrol in the essential oil of O. vulgare is electroactive on the surface of the electrode, which can explain the lower current density in the voltammograms of this essential oil …”
Section: Resultsmentioning
confidence: 92%
“…Previous studies showed that only carvacrol in the essential oil of O. vulgare is electroactive on the surface of the electrode, which can explain the lower current density in the voltammograms of this essential oil …”
Section: Resultsmentioning
confidence: 92%
“…The presence of the current peaks is evidence of the antioxidant properties of the studied extracts (Głód et al, 2014). According to the literature, the electrochemical oxidation of phenolic compounds follows a pathway that is characterized by the simultaneous transfer of electrons and protons, to give quinone products (reversible oxidation) as well as polymeric products, which remain adsorbed on the working electrode surface (irreversible oxidation) (Chiorcea‐Paquim et al, 2020; Enache & Oliveira‐Brett, 2011; Ferreira et al, 2019). It can be noticed in Figure 2 that all extracts presented an irreversible oxidation mechanism on the GCE surface, as no reduction peak was observed during the reverse voltammetric scans.…”
Section: Resultsmentioning
confidence: 99%
“…Carvacrol, being a phenolic compound, is efficient in the stabilization of free radicals and protects other biomolecules against oxidation. It acts as a direct preventive antioxidant and chain breaker and inhibits the propagation of lipid peroxidation reactions (Amorati et al 2013;Ferreira et al 2019). Elgndi et al (2017), evaluated the antioxidant activity of the essential oil from S. montana and reported an IC 50 of 5Á05 μg ml −1 , a result that was attributed to the high levels of carvacrol in this essential oil.…”
Section: Antioxidant Potential Of Essential Oilsmentioning
confidence: 99%
“…The essential oils from M. fragrans and C. flexuosus do not contain phenolic compounds. This absence of phenols might be the main reason for their low antioxidant activity because good antioxidants must be able to donate hydrogen atoms or electrons and be stabilized by the effects of hyperconjugative and resonance structures (Ferreira et al 2019). Hydrocarbons and terpene alcohols can act as indirect antioxidants, which, despite not exhibiting relevant antioxidant behaviours, increase antioxidant defenses in living systems.…”
Section: Antioxidant Potential Of Essential Oilsmentioning
confidence: 99%
See 1 more Smart Citation